Attentional demands during walking are increased by small simulated leg length discrepancy - Takada, Keisuke; Sugimoto, Miyu; Takenaka, Yuma; Sugawara, Kenichi; Suzuki, Tomotaka (Frontiers in Neuroergonomics, 2025)
IntroductionLeg length discrepancy (LLD) is known to disrupt gait symmetry and affect motor control. However, the effects of LLD-induced gait asymmetry on attention functions during walking remain unclear. Therefore, this study aimed to investigate the impact of simulated LLD and walking track on attentional demands and gait parameters in young, healthy adults.MethodsThis prospective study included participants who completed walking trials on straight (n = 14) and circular (n = 16) tracks under randomly assigned LLD conditions (no lift and 10-, 20-, 30-, and 40-mm shoe lifts). Attentional demands during walking were assessed using a simple reaction time (RT) paradigm. Gait symmetry was evaluated by step-time ratio and triaxial trunk acceleration root mean square (RMS) ratios, calculated from timing and accelerometer data. The data were analyzed using a two-way mixed analysis of variance.ResultsLLD significantly increased RT and step-time ratio compared to zero LLD. However, the circular walking track did not significantly affect RT or step-time ratio. LLD also significantly increased trunk movement asymmetry (RMS ratios). No significant interaction effects were found for all variables.ConclusionSimulated LLD significantly increased attentional demands and gait asymmetry, although the rise in attentional demands was limited in healthy participants. The circular walking track had minimal effects and did not exacerbate the challenges associated with LLD. These results provide insights into the effects of gait asymmetry caused by the degree of LLD and walking environment on human gait strategy and its associated attentional demands.